Efficacy of 0.5% levobupivacaine with clonidine 30 μg versus 0.5% levobupivacaine with 150 μg buprenorphine for USG guided interscalene brachial plexus block for shoulder, upper and middle humerus surgeries: a prospective randomized double blinded comparative study - Shaik, Rehana; Latha, Sneha; Rama Rao, Mokkarala; Paleti, Sophia (International Journal of Research in Medical Sciences, 2024)
Background: Ultrasound imaging is increasingly used for peripheral nerve blocks, offering real-time visualization of nerves, surrounding structures, and needle tips. Levobupivacaine, a local anesthetic, provides excellent intraoperative and postoperative analgesia. Buprenorphine, a partial µ-opioid receptor agonist, and clonidine, an α2 adrenergic agonist, also offer postoperative analgesia. We aimed to compare levobupivacaine with clonidine versus levobupivacaine with buprenorphine for ultrasound-guided interscalene block for shoulder and upper-arm surgeries. This study aimed to determine the onset and duration of sensory and motor block, duration of postoperative analgesia, hemodynamics, complications, and sedation. Methods: Patients scheduled for elective shoulder and upper-middle humerus surgeries received either levobupivacaine with clonidine or levobupivacaine with buprenorphine. Assessments include onset and duration of sensory and motor blockade, analgesia duration, sedation, side effects, and block quality. Onset and duration of sensory and motor blockade, and analgesia duration was analyzed using unpaired T-Test. Results: Levobupivacaine with clonidine group showed longer duration of analgesia (595±148 mins) compared to levobupivacaine with buprenorphine group (445±44.16 mins), with a significant difference (P<0.039). Conclusions: Levobupivacaine with clonidine provided excellent blockade quality, and both clonidine and buprenorphine added to levobupivacaine offered good surgical and postoperative analgesia. However, levobupivacaine with clonidine significantly prolonged postoperative analgesia compared to buprenorphine.